2019
DOI: 10.1021/acsaem.9b01611
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Studtite in Aqueous Suspension: Impact of HCO3 and Ionizing Radiation on the Dynamics of Dissolution

Abstract: In a geological repository for spent nuclear fuel, studtite (UO2)­O2(H2O)4 may form on the fuel surface when in contact with groundwater under certain conditions. Studtite has a very low solubility and could thereby reduce the reactivity of spent nuclear fuel toward radiolytic oxidants. This would inhibit the dissolution of the fuel matrix and thereby also the spreading of radionuclides. It is therefore important to investigate the stability of studtite under conditions that may influence its stability. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…In a recent paper 17 it was shown that when adding an excess amount of H 2 O 2 to an aqueous uranyl nitrite solution at ambient temperature, the precipitate formed was pure studtite as confirmed by XRD. The meta-studtite powder was synthesized in this study by adding an excess amount of H 2 O 2 to an aqueous uranyl nitrite solution at 85-90°C (controlled by using a water bath).…”
Section: Solid Phase Characterizationmentioning
confidence: 74%
See 4 more Smart Citations
“…In a recent paper 17 it was shown that when adding an excess amount of H 2 O 2 to an aqueous uranyl nitrite solution at ambient temperature, the precipitate formed was pure studtite as confirmed by XRD. The meta-studtite powder was synthesized in this study by adding an excess amount of H 2 O 2 to an aqueous uranyl nitrite solution at 85-90°C (controlled by using a water bath).…”
Section: Solid Phase Characterizationmentioning
confidence: 74%
“…The conditions for all the experiments performed and discussed in this work (including previously published data for studtite) 17 are listed in Table 1 along with solution speciation obtained from 13 C NMR characterization.…”
Section: Meta-studtite Dissolution Kinetics and The Influence Of Added H 2 Omentioning
confidence: 99%
See 3 more Smart Citations